Aplikasi Penginderan Jauh dan Sig Untuk Penetapan Tingkat Kemampuan Penggunaan Lahan (KPL) (Studi Kasus di DAS Nawagaon Maskara, Saharanpur-India) - Harjadi, Beny (Universitas Muhammadiyah Surakarta, 2007)
The land that was increasingly crowded resulting from the inhabitantsâs speeding-up pressure, required the utilisation of the land to be as efficient and as effectively as possible. For this matter must be known by the LUC (Land Use Capability) class respectively the unit of the land management, so as to be known as early as possible the obstacle factor from the land and could be done by the utilisation of the land as optimally as possible. The implementation of the LUC determination must be carried out a stage for the sake of a stage by counting LUC respectively the main factor, so as to be received by LUC-Soil, LUC-Erosion, and LUC-Slope. The next one of the three of this LUC were just counted by the value of the maximum to appoint LUC Final. LUC-Slope by being based on the Wischmeier and Smith (1978), LUC-Erosion was counted by using the quantitative MMF erosion formula (Morgan, Morgan, and Finney), and LUC-Soil by gathering the physical data the field took the form of the texture data of the land, drainage, solum and the percentage of the rock in the surface. LUC-Erosion and LUC-Soil were received by 5 LUC classes (I, II, III, IV, IV, and VI), whereas LUC-Slope was received by 7 LUC classes all of them except the V. LUC I class until IV were recommended for the agricultural crop and LUC V until VIII for the forestry crop. From 11 of Sub Watershed LUC VIII was expanded 107.54 ha to Sub Watershed Sarbar Rao and narrowest to Sub Watershed Maskara Rao (0.12 ha). On the other hand for LUC II was expanded to Sub Watershed Nawagaon Rao (1136.8 ha) and narrowest (1.51 ha) to Sub Watershed Shakumbari Rao. The location of the research in Sub Watershed Nawagaon Rao Mascara the Saharanpur city, India, with the location goegrafis from 30 o 09â 00